The Berenstain Bears' haunted hayride - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1997)
Farmer Ben takes a dim view of the cubs' plan to hold a Halloween Festival to help save his floundering family farm, and the situation is complicated when a couple of Ben's dead ancestors show up.
13
Keywords: Halloween -- Fiction; Bears -- Fiction; Ghosts -- Fiction; Farms -- Fiction